PENGARUH SIKAP, NORMA SUBJEKTIF DAN MOTIVASI TERHADAP MINAT BELI PRODUK ONLINE (Survei pada Masyarakat di Karanganyar) - Alviana Linda Kusuma; Marjam Desma Rahadhini; Retno Susanti (Universitas Slamet Riyadi, 2020)
This study aims to analyze the significance of the influence of attitudes, subjective norms and motivation on online buying interest in Karanganyar. This type of research used in this research is quantitative research. The type of data used is qualitative data and quantitative data, data sources used are primary data and secondary data. The population of this research is the people in Karanganyar who have an interest in conducting online shopping transactions with a sample of 70 respondents. Data collection techniques using questionnaires that go through the stages of testing the validity and reliability first. The regression requirements test uses the classic assumption test. Data analysis techniques used multiple linear regression analysis, t test, F test and the coefficient of determination. The results of this study indicate that the attitude of a positive and significant effect on online product purchase interest in Karanganyar communities, subjective norms have a positive and not significant effect on online product purchase interest in Karanganyar communities, and motivation has a positive and significant effect on online product purchase interest in the community in Karanganyar.